Vertical stiffness, jumps and sprint kinematics of well-trained youth female and male sprinters - Mattes, K.; Manzer, S.; Ritthaler, V.; Reischmann, M.; Buckwitz, R. (Biology of Exercise, 2018)
Maximal sprint speed and kinematic step characteristics depend on the vertical stiffness (Kvert) and jump strength, which are tested by vertical jumps with short (hopping jump (HT), drop jump (DJ)) and long (counter movement jump (CMJ)) stretch shortening cycle. The purpose was to determine the reproducibility of a HT, and the differences of sprint speed, Kvert as well as DJ and CMJ height between groups. Male junior national squad, male and female Hamburger regional squad athletes were measured in flying 30 m sprint and vertical jumps. The group differences were tested with an analysis of variance. The HT (2.2 Hz) reached a high reproducibility with ICC values >0.97 for Kvert. The group of the faster male sprinter demonstrated a shorter contact time, higher frequency with comparable flight time during sprint, a higher Kvert during HT as well as a higher jump height during DJ, but only a jump height difference of 3 cm during CMJ. The female sprinters realized a lower Kvert as the male athletes. Differences of Kvert could be tested reliable by means of HT. Kvert and the DJ height differentiated between the male groups with different sprint speed (10.04 vs. 9.19 m/s), but not the CMJ height.